Usos dos oráculos délficos em Plutarco - Maria Aparecida De Oliveira Silva (Nóesis)
Since the Ancient Greek period the sanctuary of Delphi has received Greek and Barbarian consultants and records of Roman citizens who appealed to the god Apollo to obtain oracular answers about several subjects are found in the time Plutarch lived. Thus, the purpose of this chapter is to analyze Plutarch's view on the relationship between Greeks and Romans and the oracles of Delphi.